Right connection, right insight engaging private estate managers on woodland expansion issues in times of uncertainty. (January 2023) - Bowditch, Euan. A.D.; McMorran, Rob; Smith, Melanie. A.
Abstract: Woodland expansion and related targets are central to the Scottish Forestry Strategy (2019–2029). However, planting rates over the last decade have mostly fallen short of targets and, with the majority of Scottish land in private ownership, estates could play an influential role in achieving these targets. The current political (e.g. Brexit) and ecological (e.g. climate and biodiversity emergencies) uncertainty impacting the UK presents both opportunities and potential threats to the forestry sector and environmental policies. This research used walking interviews with estate managers to gain insights into perceptions of forestry and woodland culture on private sporting estates. Co-planning of new planting areas involved discussions with a mixture of estate owners, factors and land managers from neighbouring estates, along with the researcher. The co-planning process provided scope to navigate the uncertainty between estate priorities, woodland expansion targets and wider management issues by exploring the local culture and land capability from the perspective of individual land managers. A range of constraints and opportunities were identified including the influence of deeply embedded perceptions of past and current woodland creation schemes that continue to impact the estates, market instability, and the desire to design and create beneficial integrated deer and amenity areas. These are counterbalanced with a clear passion for trees among some managers, but a relatively low interest in extensive woodland management, which was underpinned by a widespread lack of in-house forestry knowledge. The woodland planning exercise resulted in managers identifying explicit areas for potential woodland expansion on every estate, favouring mixed native woodlands with limited productive objectives. Woodfuel production was viewed as an output from early woodland thinnings with the potential to increase short-term profitability and offset management costs. This paper highlights that strengthening personal connections between land managers and woodland management, through knowledge building and contact with up-to-date forestry knowledge from a trusted provider, could further opportunities for expanding and enhancing woodland culture, and become a more significant part of the rationale that drives decision-making. Facilitating local knowledge of the estate and local community involvement in woodland design and planning, even on a small-scale, offers potential to support the expansion and integration of woodland on some private estates that have lost or reduced woodland culture. Highlights: Private estate managers are influenced by past and current woodland design, as well as expected value of woodlands. Uncertainty such as climate change and BREXIT presents opportunities for land use integration but can also impede action. Face-to-face engagement and co-planning can increase the likelihood of managers implementing woodland expansion. Loss of woodland management knowledge and local experience on estates and communities influence resistance toward expansion. Perceived challenges relating to long-term investment, space and relative value, outweigh perceived benefits. Changing narratives from targets to primary benefits, practicalities and personal motivations facilitates greater acceptance.